PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) DAN SUPPLY CHAIN MANAGEMENT (SCM) TERHADAP KINERJA PERUSAHAAN (STUDI EMPIRIS PADA PT. WAHANA WIRAWAN RIAU) PEKANBARU - Hutagalung Windy Frans; Daulay Nauli Iwan; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The company who has intention to improve their competitiveness in this tough industrycompetitive era must concern about the supply chain, and also can produce quality products. This study aims to determine the effects of Total Quality Managementand Supply Chain Management to Organizational Performance at PT. Wahana Wirawan Riau. The sample in this study includes employees at PT. Wahana Wirawan Riau, totaling 30 people. Primary data was collected by questionnaire as an instrument to prove the result of the research , to test the hypothesisin this study is using multiple linear regression with SPSS (Statistical Program for Social Sciences). The sampling technique is a method that has been selected with an interview and distributing questionnaire directly. The result showed that: 1) There is a positive and significant effect of Total Quality Management on Organizational Performance at PT. Wahana Wirawan Riau, 2) There is a positive and significant effect of Supply Chain Management on Organizational Performance at PT. Wahana Wirawan Riau, 3) There is a positive and significant effect of Total Quality Management and Supply Chain Management on Organizational Performance at PT. Wahana Wirawan Riau.Keywords: Total Quality Management, Supply Chain Management, Organizational Performance